Children discharged from neonatal intensive care: implications for the social care networks - Nascimento, Maria Licele do; Pieszak, Greice Machado; Arrué, Andrea Moreira; Carvalho, Sandra Ost Rodrigues Martins (Rev Rene, 2016)
Objective: to understand the social care networks of children discharged from Neonatal Intensive Care Unit. Methods: qualitative study conducted in the home of six families of seven children. In data collection, authors used the triangulation of techniques with thematic content analysis. Results: family composition is nuclear, social networks are formed by the support of family, leisure and spiritual ties, by school and hospital institutions. The families reported the challenges of caring for a premature baby, and the main care demands were respiratory, motor and cognitive. The non-effective communication between professionals and family showed negative impact on hospitalization and home care. Conclusion: social care networks for children discharged from the Neonatal Intensive Care unit proved to be disjointed and health care for children and family proved to be fragmented.